2021
DOI: 10.1080/21655979.2021.1948487
|View full text |Cite
|
Sign up to set email alerts
|

CircRAB3IP upregulates twist family BHLH transcription factor (TWIST1) to promote osteosarcoma progression by sponging miR-580-3p

Abstract: Circular RNAs (circ RNAs) have been found to play an important role in cancer development. However, the role of circRAB3IP in osteosarcoma (OS) is unclear.In the present study, We found that circRAB3IP was highly expressed in OS tissues and OS cells. High levels of circRAB3IP was correlated with advanced TNM stage, distant metastasis. CircRAB3IP knockdown inhibited cell proliferation, migration, and invasion. Moreover, circRAB3IP directly binds to miR-580-3p. TWIST1 is directly targeted by miR-580-3p. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…For example, miR-580-3p repressed melanoma cell malignancy through the LHFPL3-AS1/miR-580-3p/ STAT3 axis 44 . MiR-580-3p inhibited osteosarcoma cell growth and motility through the circRAB3IP/miR-580-3p/TWIST1 pathway 45 . In particular, Sun et al 46 showed that miR-580 expression was lower in patients with acute kidney injury than in patients without acute kidney injury.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, miR-580-3p repressed melanoma cell malignancy through the LHFPL3-AS1/miR-580-3p/ STAT3 axis 44 . MiR-580-3p inhibited osteosarcoma cell growth and motility through the circRAB3IP/miR-580-3p/TWIST1 pathway 45 . In particular, Sun et al 46 showed that miR-580 expression was lower in patients with acute kidney injury than in patients without acute kidney injury.…”
Section: Discussionmentioning
confidence: 98%
“…For example, miR‐580‐3p repressed melanoma cell malignancy through the LHFPL3‐AS1/miR‐580‐3p/STAT3 axis 44 . MiR‐580‐3p inhibited osteosarcoma cell growth and motility through the circRAB3IP/miR‐580‐3p/TWIST1 pathway 45 . In particular, Sun et al 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-580 inhibited cell motility in breast cancer by downregulating TWIST1, implying that miR-580 functioned as a tumor suppressor [ 30 ]. Moreover, circRAB3IP has been revealed to act as the sponge of miR-580-3p to promote TWIST1 expression in osteosarcoma [ 31 ]. However, the correlation between miR-580 and AML has not been explicated.…”
Section: Discussionmentioning
confidence: 99%
“…miR-580-3p is an inhibitor of Twist1, which reduces the malignancy of osteosarcoma cells. However, circRAB3IP reduces miR-580-3p expression to upregulate Twist1 and promote osteosarcoma malignancy [ 167 ]. CircRNA PVT1 is upregulated in cancers and stimulates the Wnt4/β-catenin axis to increase carcinogenesis [ 168 ].…”
Section: Circrnas Regulating Emt-tfs In Cancersmentioning
confidence: 99%